INTERVENÇÕES DE PSICÓLOGOS NAS UNIDADES BÁSICAS DE SAÚDE DO GRANDE ABC - Velasques, Márcia Barbosa (2003)
This work has as its objective a survey of interventions realized by psychologists that work in the Basic Health Units (UBS) of Greater ABC, as well as presenting a profile of these professionals. This survey covers the Region of Greater ABC, and is based in the tradition of research regarding Psychology as a profession during the last thirty years. The analysis of research data is accomplished via four defined categories based on the exercise of this profession in the UBS's: 1) the environment of services provided, from the individual to the collective; 2) services provided in consultation in a public institution; 3) emphasis on work that includes the range between the "curative" and the preventive; 4) area of actuation, from mental health to the psychology of health. The results presented are based on thirty-eight interviews realized with psychologists of the UBS's of the Region of Greater ABC, during the year 2002, that bring to light the difficulties involved with these activities. Political, economic and social difficulties, that are independent of the desires of the professionals, are noted. Beyond these factors, difficulties related to professional training and the understanding of the role and function of the psychologist in the UBS's are identified.